Hepatitis B Virus X Upregulates HuR Protein Level to Stabilize HER2 Expression in Hepatocellular Carcinoma Cells. (27th February 2014) - Hung, Chao-Ming; Huang, Wei-Chien; Pan, Hsiao-Lin; Chien, Pei-Hsuan; Lin, Chih-Wen; Chen, Lei-Chin; Chien, Yu-Fong; Lin, Ching-Chiao; Leow, Kar-Hee; Chen, Wen-Shu; Chen, Jhen-Yu; Ho, Chien-Yi; et al.
Abstract : Hepatitis B virus- (HBV-) associated hepatocellular carcinoma (HCC) is the most common type of liver cancer. However, the underlying mechanism of HCC tumorigenesis is very complicated and HBV-encoded X protein (HBx) has been reported to play the most important role in this process. Activation of downstream signal pathways of epidermal growth factor receptor (EGFR) family is known to mediate HBx-dependent HCC tumor progression. Interestingly, HER2 (also known as ErbB2/Neu/EGFR2) is frequently overexpressed in HBx-expressing HCC patients and is associated with their poor prognosis. However, it remains unclear whether and how HBx regulates HER2 expression. In this study, our data showed that HBx expression increased HER2 protein level via enhancing its mRNA stability. The induction of RNA-binding protein HuR expression by HBx mediated the HER2 mRNA stabilization. Finally, the upregulated HER2 expression promoted the migration ability of HBx-expressing HCC cells. These findings deciphered the molecular mechanism of HBx-mediated HER2 upregulation in HBV-associated HCC.